Hybrid-type strigolactone analogues derived from auxins - Blanco-Ania, Daniel; Mateman, Jurgen J; Hýlová, Adéla; Spíchal, Lukáš; Debie, Luc M; Zwanenburg, Binne (Pest management science, 2019)
BACKGROUND: Strigolactones (SLs) have a vast number of ecological implications because of the broad spectrum of their biological activities. Unfortunately, the limited availability of SLs restricts their applicability for the benefit of humanity and renders synthesis the only option for their production. However, the structural complexity of SLs impedes their economical synthesis, which is unfeasible on a large scale. Synthesis of SL analogues and mimics with a simpler structure, but with retention of bioactivity, is the solution to this problem. RESULTS: Here, we present eight new hybrid-type SL analogues derived from auxin, synthesized via coupling of auxin ester [ethyl 2-(1H-indol-3-yl)acetate] and of ethyl 2-phenylacetate with four D-rings (mono-, two di- and trimethylated). The new hybrid-type SL analogues were bioassayed to assess the germination activity of seeds of the parasitic weeds Striga hermonthica, Orobanche minor and Phelipanche ramosa using the classical method of counting germinated seeds and a colorimetric method. The bioassays revealed that analogues with a natural monomethylated D-ring had appreciable to good activity towards the three species and were the most active derivatives. By contrast, derivatives with the trimethylated D-ring showed no activity. The dimethylated derivatives (2,4-dimethyl and 3,4-dimethyl) were slightly active, especially towards P. ramosa. CONCLUSIONS: New hybrid-type analogues derived from auxins have been prepared. These analogues may be attractive as potential suicidal germination agents for parasitic weed control because of their ease of preparation and relevant bioactivity. © 2019 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.
Keywords: semena rostlinná; strigolactone analogues; Plant Weeds; auxins; klíčení; Weed Control; Orobanchaceae; Germination; kyseliny indoloctové; plevel; Striga; Seeds; kontrola plevele; Indoleacetic Acids; suicidal germination; Lactones; laktony; Orobanche; strigolactones